2017
DOI: 10.1016/j.placenta.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Review: Placental mitochondrial function and structure in gestational disorders

Abstract: 22The aetiology of many gestational disorders is still unknown. However, insufficient trans-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
149
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(157 citation statements)
references
References 75 publications
4
149
2
2
Order By: Relevance
“…In rats, eIF2 signalling was also shown to be heavily involved in the regulation of placental and foetal development . Likewise, oxidative phosphorylation and mitochondrial dysfunction have been associated with a range of gestational disorders . Mitochondrial dysfunction could also indicate an impairment of the antiviral immune response .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats, eIF2 signalling was also shown to be heavily involved in the regulation of placental and foetal development . Likewise, oxidative phosphorylation and mitochondrial dysfunction have been associated with a range of gestational disorders . Mitochondrial dysfunction could also indicate an impairment of the antiviral immune response .…”
Section: Discussionmentioning
confidence: 99%
“…32 Likewise, oxidative phosphorylation and mitochondrial dysfunction have been associated with a range of gestational disorders. 33 Mitochondrial dysfunction could also indicate an impairment of the antiviral immune response. 34 It is known that some viruses attack the host cell mitochondrial network as a form of immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…); however, mitochondrial content in the placenta has been shown altered in a range of pathologies (Holland et al . ). Maternal glucocorticoids have been shown to reduce mitochondrial content in fetal heart tissues (Richards et al .…”
Section: Discussionmentioning
confidence: 97%
“…Cellular mitochondrial content is adaptive and can change in response to cellular damage. Skeletal muscle mitochondrial content is increased in response to exercise to enhance tissue function (Broskey et al 2014); however, mitochondrial content in the placenta has been shown altered in a range of pathologies (Holland et al 2017). Maternal glucocorticoids have been shown to reduce mitochondrial content in fetal heart tissues (Richards et al 2014), and in vitro studies have demonstrated decreased mitochondrial content in endothelial cells exposed to glucocorticoids (Gero & Szabo, 2016).…”
Section: Effects Of Corticosterone On Mitochondrial Functionmentioning
confidence: 99%
“…15,16 The mitochondria control subjects many critical cell functions, which include the production of cellular energy, adenosine triphosphate, by the coupling of OP to cell respiration. 17–19 Oxidative stress-induced damage to mitochondrial structural elements (eg, lipid membrane) alters mitochondrial gene expression and promotes a deficiency in OP, 20 which results in mitochondrial dysfunction. Hundreds of nuclear DNA genes across the chromosome regulate MB and maintain mitochondrial structure and function by regulating OP.…”
Section: Introductionmentioning
confidence: 99%